Clinical efficacy of EDTA ultrasonic activation in the reduction of endotoxins and cultivable bacteria - Herrera, D. R.; Martinho, F. C. [UNESP]; de-Jesus-Soares, A.; Zaia, A. A.; Ferraz, C. C.R.; Almeida, J. F.A.; Gomes, B. P.F.A. (Wiley, 2017)
Aim: This clinical study was conducted to investigate the influence of 17% ethylenediaminetetraacetic acid (EDTA) ultrasonic activation after chemomechanical preparation (CMP) on eliminating/reducing oral bacterial lipopolysaccharides (known as endotoxins) and cultivable bacteria in teeth with pulp necrosis and apical periodontitis. Methodology: Samples were taken from 24 root canals at several clinical periods: S1 – before CMP; S2 – after CMP; S3 – after EDTA: G1 – with ultrasonic activation (n = 12) and G2 – without ultrasonic activation (n = 12). Root canals were instrumented using Mtwo rotary files. Culture techniques were used to determine the number of colony-forming units (CFU). Limulus amebocyte lysate (LAL) was used to measure endotoxin levels. Friedman's and Wilcoxon signed-rank tests were used to compare the amount of bacteria and endotoxin levels in each period (P < 0.05). Results: Endotoxins and cultivable bacteria were recovered in 100% of the initial samples (S1). CMP was effective in reducing endotoxins and bacterial load (all with P < 0.05). Higher values of endotoxin reduction were achieved with EDTA ultrasonic activation [G1, 0.02 EU mL−1 (range 0.01–0.75)] compared with the no activation group [G2, 1.13 EU mL−1 (range 0.01–8.34)] (P < 0.05). Regarding bacterial reduction, no statistically significant difference was found in S3, regardless of the group (G1, G2, P > 0.05). Conclusions: Chemomechanical preparation was effective in reducing bacteria and endotoxins, but could not completely eliminate them. The ultrasonic activation of EDTA was effective in further reducing endotoxin levels in the root canals of teeth with pulp necrosis and apical periodontitis.
Keywords: EDTA; endotoxin; root canal infection; ultrasonic